Sequencing of the coding regions of GNBIL on chromosome 22q11.2 as a risk gene of schizophrenia. (June 2021) - Wang, Yu-Yuan; Hsu, Shih-Hsin; Tsai, Hsin-Yao; Cheng, Min-Chih
Highlights: We resequenced all protein-coding regions of the GNB1L. Common SNPs of the GNB1L are not associatedwith schizophrenia. Three rare missense mutations were identified in patients with schizophrenia only. Abstract: GNB1L haploinsufficiency caused by 22q11.2 deletion syndrome may contribute to schizophrenia pathophysiology. We resequenced the protein-coding sequences of GNB1L in 553 patients with schizophrenia and 535 controls from Taiwan. Four common single-nucleotide polymorphisms showed no association with patients with schizophrenia. We identified 17 rare missense mutations, including three that were schizophrenia-associated and predicted as pathogenic (p.R57W, p.G68S, and p.R265C). Given that rare mutations with high penetrance contribute to schizophrenia, missense mutations of GNB1L might increase the risk of schizophrenia in some patients.